3z+2(6-z)=-(z-1)+1

Simple and best practice solution for 3z+2(6-z)=-(z-1)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3z+2(6-z)=-(z-1)+1 equation:


Simplifying
3z + 2(6 + -1z) = -1(z + -1) + 1
3z + (6 * 2 + -1z * 2) = -1(z + -1) + 1
3z + (12 + -2z) = -1(z + -1) + 1

Reorder the terms:
12 + 3z + -2z = -1(z + -1) + 1

Combine like terms: 3z + -2z = 1z
12 + 1z = -1(z + -1) + 1

Reorder the terms:
12 + 1z = -1(-1 + z) + 1
12 + 1z = (-1 * -1 + z * -1) + 1
12 + 1z = (1 + -1z) + 1

Reorder the terms:
12 + 1z = 1 + 1 + -1z

Combine like terms: 1 + 1 = 2
12 + 1z = 2 + -1z

Solving
12 + 1z = 2 + -1z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add 'z' to each side of the equation.
12 + 1z + z = 2 + -1z + z

Combine like terms: 1z + z = 2z
12 + 2z = 2 + -1z + z

Combine like terms: -1z + z = 0
12 + 2z = 2 + 0
12 + 2z = 2

Add '-12' to each side of the equation.
12 + -12 + 2z = 2 + -12

Combine like terms: 12 + -12 = 0
0 + 2z = 2 + -12
2z = 2 + -12

Combine like terms: 2 + -12 = -10
2z = -10

Divide each side by '2'.
z = -5

Simplifying
z = -5

See similar equations:

| 3a-10=-25 | | 28*x=(4x-2)*7 | | 5-8x+x=40 | | d(3d-15)=0 | | Y=.5+8 | | -8m-[2(10-5m)+15]=9m | | 45a^4b^3/15a^4b^2 | | r^2+81=r^2+6r+9 | | 2(7c-1)-18=12c+2 | | 7.4X=-52.54 | | -4.6X+1.1=-21.9 | | 2(c-1)-18=12c+2 | | 6sin^2+5cos=2 | | (2/3)^5= | | X-1=9.58 | | 18-(4m+4)=4+2m-14 | | 98/6 | | 2x-20=5x+9 | | 12x+0.5x+x=40 | | 2(f-8)=-30 | | 10(s-5)=-152 | | lnx=(1/8) | | 4k^2=9k | | 4(t+3)=-4 | | 7(25x+2)=0 | | 51.20=128-r*128 | | (7t+2)(t^2-5t-3)=0 | | 7(x+49)+28=14x-42+7x | | 3z^2-x-6=0 | | 2x=0.8x+54 | | 2x=0.8+54 | | 51.20=128-r^128 |

Equations solver categories